INTERNATIONAL MARKETING OPPORTUNITIES THROUGH FASHION INDUSTRY MARKETING STRATEGIES (Marketing Journal, 2025)
This article analyzes the role of marketing strategies in the internationalization of the fashion industry within a theoretical framework. Core marketing components — brand, product, price, distribution, and communication — are evaluated in terms of their adaptability in global contexts. Regional approaches are comparatively assessed, and a strategic structure is proposed based on a conceptual model. Content analysis and comparative methodology are applied. Based on the findings, the impact of digital techn ology integration on effectiveness is identified, and strategic recommendations are formulated.
Keywords: fashion industry; marketing strategy; international market; digital communication; adaptation; conceptual model. 512